1992
DOI: 10.1002/bsl.2370100112
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism of disordered offenders who were conditionally vs. unconditionally released

Abstract: Postinstitutional arrests and state hospitalizations of 191 patients placed on conditional release (CONREP group) were compared to those of 44 patients released &om the same califorpia state hospital with no aftercare due to expiration of commiment terms (MAXOUT group). The two groups were not randomly determined but were comparable in demographic characteristics and rates of preprogram arrest. The CONREP group had a significantly lower community-period arrest rate than did the MAX-OUT group (p < .001). Surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Therefore, in NGRI populations, typically two outcome metrics related to "failure" are being used: the acquisition of new criminal charges and/or conditional release revocation due to criminal acts or rule violations. Literature demonstrates that revocations for rule violations are higher than revocations for acquisition of new criminal charges (Vitacco, Vauter, Erickson, & Ragatz, 2014;Wiederanders, 1992). Revocation rates of rule violations range from 5% to 49% (Bertman-Pate et al, 2004;Callahan & Silver, 1998;Green et al, 2014;Manguno-Mire, Coffman, DeLand, Thompson, & Myers, 2014;Vitacco et al, 2008;Vitacco et al, 2014;Wiederanders, Bromley, & Choate, 1997) over different follow-up periods ranging from 1.7 to 5.1 years.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, in NGRI populations, typically two outcome metrics related to "failure" are being used: the acquisition of new criminal charges and/or conditional release revocation due to criminal acts or rule violations. Literature demonstrates that revocations for rule violations are higher than revocations for acquisition of new criminal charges (Vitacco, Vauter, Erickson, & Ragatz, 2014;Wiederanders, 1992). Revocation rates of rule violations range from 5% to 49% (Bertman-Pate et al, 2004;Callahan & Silver, 1998;Green et al, 2014;Manguno-Mire, Coffman, DeLand, Thompson, & Myers, 2014;Vitacco et al, 2008;Vitacco et al, 2014;Wiederanders, Bromley, & Choate, 1997) over different follow-up periods ranging from 1.7 to 5.1 years.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 97%
“…However, regimens of treatment and supervision are seldom reported or quantified, and studies of the effectiveness of conditional release programs are difficult to compare (Wiederanders et al, 1997). Although there has been past research confirming that postrelease supervision and community treatment can reduce recidivism (e.g., Wiederanders, 1992), a systematic review shows that little empirical evidence exists to conclude that long term supervision remains effective (van Gestel, van der Knaap, & Hendriks, 2006). In addition, studies have shown that recidivism can be reduced by implementing (forensic) ambulatory care after release (i.e., Home Office restrictions requiring patients to accept supervision and treatment following discharge: Coid, Hickey, Kahtan, Zhang, & Yang, 2007; specialised forensic outpatient clinics: SchmidtQuernheim & Seifert, 2014).…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 97%
“…This broad range highlights the difficulties in comparing studies with different follow-up periods, from different time periods and jurisdictions, which can have quite different legalisation, mental health, and criminal justice systems. The importance of such factors is illustrated in the research that reported that higher conditional leave revocation rates were associated with lower reoffending rates and vice versa (Parker, 2004;Wiederanders, 1992). According to this view, revocation acts as a preventative measure before reoffending can occur.…”
Section: Reoffending and The Insanity Defencementioning
confidence: 93%
“…Another empirical study concluded that individuals who received an outpatient commitment showed fewer rehospitalizations compared to patients who were discharged without an outpatient commitment (Munetz, Grande, Kleist, & Peterson, 1995). Widerlanders (1992) also found that conditional release contributed to a decrease of recidivism and violent behavior in forensic patients (see also McGreevy, Steadman, Dvoskin, & Dollard, 1991). Other efforts to employ IOC at discharge have shown success, as well (for a review, see Hiday, 1996).…”
Section: Evaluating Involuntary Outpatient Commitment At Dischargementioning
confidence: 97%